Aucklandiae Radix and Vladimiriae Radix: A systematic review in ethnopharmacology, phytochemistry and pharmacology. (15th November 2021) - Huang, Zecheng; Wei, Chunlei; Yang, Ke; Yu, Ziwei; Wang, Zhanguo; Hu, Huiling
Abstract: Ethnopharmacological relevance: Aucklandiae Radix (AR) and Vladimiriae Radix (VR), as commonly used traditional Chinese herbal medicine, were widely used in the treatment of gastrointestinal diseases. The two herbal medicines were warm, pungent and bitter. They entered the spleen, stomach, large intestine and gallbladder meridians, and had the effect of promoting qi circulation to relieve pain. It is usually used for chest and hypochondrium, abdominal fullness and pain, tenesmus, indigestion, and warming the middle to harmonize the stomach in clinically. Aim of this review: To provide a reference for the identification of traditional use, the material basis of efficacy and preclinical research between AR and VR, this review systematically summarized the similarities and differences in ethnopharmacology, phytochemistry and modern pharmacology. Materials and methods: The literature information was collected systematically from the electronic scientific databases, including PubMed, Science Direct, Google Scholar, Web of Science, Geen Medical, China National Knowledge Infrastructure, as well as other literature sources, such as classic books of herbal medicine, master's thesis, doctoral thesis. Results: In the plateau areas of Sichuan Province, VR used to be regarded as substitute or local habit for AR, which is regularly used for chest, abdominal fullness and pain, diarrhea, and other related diseases. In Chinese Pharmacopoeia (ChP) 2020 edition, 145 prescription preparations with AR were collected, such as Xianglian Wan, Muxiang Shunqi Wan, Liuwei Muxiang San. However, only one prescription preparation (Jiuxiang Zhitong Wan) contained VR. Additionally, 237 and 254 chemical components were separately isolated and identified from AR and VR, 69 kinds of compounds were common among them, and the significant differences were presented in sesquiterpene lactones, monoterpenoids, triterpenoids and phenylpropanoids. Moreover, Costunolide (COS) and Dehydrocostus lactone (DEH), two main research objects of modern pharmacology, showed multiple pharmacological activities. Not only could they inhibit the activity of some cancer cells (such as breast cancer and leukemia cells), but they regulated the levels of various inflammatory factors (including TNF- α, NF- κ B, IL-1 β, IL-6) and repressed the growth and reproduction of various microorganisms (like Helicobacter pylori, Staphylococcus aureus ). Conclusion: COS and DEH as the common active components, provide a certain basis for local medicine about the substitution of VR for AR in Sichuan province of China in the past. In addition, the sesquiterpenoids are the main common compounds in AR and VR by collecting and collating a large number of literature and various data websites. Furthermore, AR and VR have significant differences in ethnopharmacology and phytochemistry, especially in sesquiterpene lactones, monoterpenoids, triterpenoids and phenylpropanoids, and are probably viewed as reference of a separate list of AR and VR in Chinese Pharmacopoeia. Graphical abstract: Image 1